Avifauna nos parques eólicos do extremo sul do Brasil - Falavigna, Tamara Justo (Universidade do Vale do Rio dos Sinos, 2019)
Wind energy has definitely been integrated into the world energy matrix and there are public policies for the continuity of its development. Brazil also adhered to the use of this source and Rio Grande do Sul (RS) occupies the fourth place in installed capacity, exploring approximately 1.7% of its wind potential in 18 wind farms in commercial operation. A main issue observed in the discourse in support of wind energy is the search for sustainable development, since the source offers environmental benefits, such as: reducing the need for non-renewable sources, like coal and oil, with a consequent reduction of water use and reduction of habitat destruction. However, the installation of this type of energy also represents a generation of negative impacts, especially on the community of birds by the collision with the wind turbines. The assessment of this impact is commonly done through fatality records and many models have been deployed to predict this risk in an attempt to balance the risks and benefits in order to minimize adverse environmental effects. Thus, the objectives of this work were: (i) to evaluate the species composition, richness and bird mortality in the wind farms in RS, comparing the regions of implantation; (ii) to verify how the technical characteristics of the wind farms, environmental factors and landscape affect the mortality rate; (iii) to evaluate three phases of a wind farm: pre-construction, construction and operation regarding the composition of bird species, environment guilds and mortality, and (iv) propose a collision risk index. In this way, secondary avifauna data were obtained from fauna monitoring reports submitted to the RS environmental agency of 11 operating wind farms located in three regions: Coxilha de Santana, North Coast and South Coast. A total of 315 bird species were registered in all wind farms, the majority being resident, insectivorous and from open area. The species composition is different in the three regions, however, for mortality this pattern is not repeated. The technical characteristics of the wind farms and the evaluated environmental factors do not have relation with the species that died, although when the landscape structure is added this pattern changes. The average mortality rate observed was 0.494 individual/turbine/year and the mortality rate estimated was 1.154, being similar with results found in other wind farms in the United States and Spain. The evaluation of the composition of species in the three phases of a wind farm showed that the pre-construction phase is different from the four years of operation, indicating a possible impact of the operation of the wind farm on the bird community. The results show that care must be taken when analyzing the effects of wind farms on birds, especially in the absence of long-term studies to confirm impact trends. The proposed risk index considered only morphological and ethological characteristics of the species. However, the collisions that were recorded and evaluated in this study are mostly occurring with species that present medium to low collision risk and what would explain the collisions would not be the species themselves, but the structure of the landscape and some characteristics of wind farms. Thus, it is fundamental to develop studies to improve or to unravel a new index, testing the inclusion of different factors, in order to lead to results closer to reality, seeking the best conservation of avifauna in wind farms.
Keywords: Impacto ambiental; Energia renovável; Colisão; Taxa de mortalidade; Environmental impact; Renewable energy; Collision; Mortality; ACCNPQ::Ciências Biológicas::Biologia Geral